2019
DOI: 10.1016/j.ophtha.2019.03.050
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 3, Randomized, Double-Masked Study of OTX-101 Ophthalmic Solution 0.09% in the Treatment of Dry Eye Disease

Abstract: Purpose: To evaluate the safety and efficacy of OTX-101, a novel aqueous nanomicellar formulation of cyclosporine (0.09%), in the treatment of patients with dry eye disease (DED).Design: A randomized, multicenter, vehicle-controlled, double-masked, phase 3 clinical trial.Participants: Adults (18e90 years of age) with a history and clinical diagnosis of DED, a global symptom score of 40 or more (range, 0e100), and a lissamine green conjunctival staining score of 3 or more and 9 or less (range, 0e12) in at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 11 publications
(19 reference statements)
1
81
0
Order By: Relevance
“…28 Phase 2b/3 and 3 clinical studies showed that twicedaily administration of OTX-101 0.09% was superior to vehicle in increasing tear production and improving ocular signs from baseline, including conjunctival and corneal staining in patients with KCS. 29,30 Importantly, improvement in these objective signs was seen at and after 4 weeks of therapy. 29,30 In a pooled analysis of phase 2b/3 and 3 trials, least square mean change from baseline for total corneal staining on day 28 was −0.9 and −0.5 for OTX-101 0.09% and vehicle, respectively (P = 0.0008).…”
Section: Available Ophthalmic Csa Formulationsmentioning
confidence: 93%
See 4 more Smart Citations
“…28 Phase 2b/3 and 3 clinical studies showed that twicedaily administration of OTX-101 0.09% was superior to vehicle in increasing tear production and improving ocular signs from baseline, including conjunctival and corneal staining in patients with KCS. 29,30 Importantly, improvement in these objective signs was seen at and after 4 weeks of therapy. 29,30 In a pooled analysis of phase 2b/3 and 3 trials, least square mean change from baseline for total corneal staining on day 28 was −0.9 and −0.5 for OTX-101 0.09% and vehicle, respectively (P = 0.0008).…”
Section: Available Ophthalmic Csa Formulationsmentioning
confidence: 93%
“…29,30 Importantly, improvement in these objective signs was seen at and after 4 weeks of therapy. 29,30 In a pooled analysis of phase 2b/3 and 3 trials, least square mean change from baseline for total corneal staining on day 28 was −0.9 and −0.5 for OTX-101 0.09% and vehicle, respectively (P = 0.0008). 31 Similarly, there was a significant reduction in total conjunctival staining from baseline (P = 0.0316) on day 28 compared with the vehicle.…”
Section: Available Ophthalmic Csa Formulationsmentioning
confidence: 93%
See 3 more Smart Citations